Qualitative Analysis of Non-Feather Distributions as a Phenotype and Genotype in the Indonesian Indigenous Naked Neck Chickens - Ariyadi , B.; Sidadolog, J.H.P.; Harimurti, S.; Sudaryati, S.; Wihandoyo (International Journal of Poultry Science, 2015)
This study was conducted to analyze the relationship between the condition of non-feather distributions and its genetically traits as a multiple allele of the feather condition in the Indonesian indigenous naked neck chickens. Eight males Indonesian naked neck chickens were paired with the five females that had the different condition of non-feathers distribution, namely non-feathers on the neck only (30%); non-feathers on the crop and breast (60%) and non-feathers on the neck, crop, breast and the back of body (90%). Assuming that the non-feathers distribution was caused by a multiple alleles of Na gene and developing of distribution were caused by Na+ as a multiple alleles of Na gene. This study revealed the effect of multiple allele Na+ on the distribution of non-feather areas in the chicken bodies. Analysis of inheritance was conducted by Mendelian heredity with chi-square (X2) analysis. The results, in the Indonesian naked neck chicken, showed that the distribution of non-feathers areas from the neck to the back of body might be caused by genetic of Na+Na+ and Na+Na. The non-feather distribution areas in the crop, breast and the thigh might be genetics effect of Na+na and NaNa (90%). The non-feather distribution areas in the neck or in the crops might be genetics effect of Nana. The normal feathers of chicken might be effect of recessive gene of nana. Moreover, the study showed that the Indonesian naked neck chicken had a lower productivity, higher embryonic mortality and lower hatchability.